Manhaj as Epistemological Foundation: Rethinking Da'wah Messages in Salafi Communities, West Sumatra - Afandi, Yusuf; Bukhari; Andri Ashadi (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
This article aims to identify and conceptualize the “manhaj” message as an epistemological category within Salafi da’wah practices in West Sumatra. This study is an extension of existing theories of da’wah messages, which have so far been limited to the aspects of 'aqidah, sharia, and akhlak, while the aspects that shape religious practice and the formation of a framework of thought in understanding religious teachings have not yet received attention from experts and academics in the field of da’wah. Using a qualitative exploratory-conceptual approach, the author collected data from various studies on Salafi da'wah in West Sumatra through interviews, observations, and documentation of various online and offline studies conducted by the Salafi da'wah community. This study found that the "manhaj" is one of the most important messages in Salafi da'wah activities. This message emphasizes following the Sunnah (ittiba` as-sunnah), rejecting innovation (bid'ah), issuing warnings (tahdzir), and reinforcing the authority of specific scholars as the primary reference in religious practice. This manhaj message not only serves as da'wah material in da'wah studies but also shapes an individual's way of thinking in understanding, practicing, and evaluating their religious practices. Thus, the manhaj message functions as the epistemological foundation of Salafi da'wah. This study concludes that the concept of "manhaj" is a significant category in the study of da'wah, expanding the analytical framework for da'wah messages from a normative to an epistemological dimension, and making a theoretical contribution to the development of da'wah studies in the contemporary era.